2023
DOI: 10.1038/s41420-023-01503-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered muscle niche contributes to myogenic deficit in the D2-mdx model of severe DMD

Abstract: Lack of dystrophin expression is the underlying genetic basis for Duchenne muscular dystrophy (DMD). However, disease severity varies between patients, based on specific genetic modifiers. D2-mdx is a model for severe DMD that exhibits exacerbated muscle degeneration and failure to regenerate even in the juvenile stage of the disease. We show that poor regeneration of juvenile D2-mdx muscles is associated with an enhanced inflammatory response to muscle damage that fails to resolve efficiently and supports the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been recently reported that targeting the TGF-β signaling in D2. mdx mice reduce muscle degeneration, calcification and fibrosis by blocking FAP accumulation ( Mázala et al, 2023 ). Similarly, inhibition of Rho-kinase, which is highly expressed in dystrophic muscles ( Zhao et al, 2003 ) reduces FAP PDGF-AA expression, improves muscle function, and reduces fibrosis ( Fernández-Simón et al, 2022 ).…”
Section: Cellular and Molecular Crosstalk In Muscle Regeneration And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been recently reported that targeting the TGF-β signaling in D2. mdx mice reduce muscle degeneration, calcification and fibrosis by blocking FAP accumulation ( Mázala et al, 2023 ). Similarly, inhibition of Rho-kinase, which is highly expressed in dystrophic muscles ( Zhao et al, 2003 ) reduces FAP PDGF-AA expression, improves muscle function, and reduces fibrosis ( Fernández-Simón et al, 2022 ).…”
Section: Cellular and Molecular Crosstalk In Muscle Regeneration And ...mentioning
confidence: 99%
“…While TNF is responsible for efficient FAP clearance, the subsequent wave of TGF-β1 blocks the pro-apoptotic effects of TNF and ensures an efficient tissue regeneration ( Lemos et al, 2015 ). Indeed, in dystrophic muscle environments, where a large subset of MPs expresses both TNF and TGF-β1, this ordered transition is disrupted and the muscle presents higher number of FAPs that is correlated with increased fibrosis ( Lemos et al, 2015 ), which also results in a poor regenerative myogenesis and greater muscle degeneration ( Mázala et al, 2023 ). Additionally, in dystrophic muscles dysregulated MPs secrete higher levels of growth factors and latent TGF-β1 that is subsequently activated by FAP-secreted enzymes, further promoting FAPs proliferation and ECM component release ( Juban et al, 2018 ; Wang et al, 2023 ).…”
Section: Cellular and Molecular Crosstalk In Muscle Regeneration And ...mentioning
confidence: 99%